Studying the influence of Solcoseryl drug and vitamin C on the inflammatory reaction and proliferation of fibroblastic cells in the filed of polypropylene endoprosthesis implantation - Viktor A. Lazarenko; Sergey V. Ivanov; Tatyana A. Pankrusheva; Ilya S. Ivanov; Evgeny G. Ob'edkov; Galina N. Goryainova; Lyubov A. Kopteva; Marina S. Chekmareva; Inna A. Ivanova; Natalya Ju. Ob'edkova (Belgorod National Research University, 2021)
Introduction: Applying a coating on hernia endoprosthesis prevents recurrent anterior abdominal wall hernias, reduces inflammatory response and stimulates reparative processes in the area of its implantation. The aim of investigation was to study the effect of Solcoseryl and Vitamin C in a collagen-stimulating coating of hernioendoprosthesis on a morphological picture in anterior abdominal wall plastic surgery. Materials and methods: The study was performed on 180 laboratory mice divided into three groups of 60 animals each: the first group animals were implanted with polypropylene endoprostheses without a collagen-stimulating coating, the second group animals - polypropylene endoprostheses with a collagen-stimulating coating with Vitamin C, and the third group animals - polypropylene endoprostheses with a collagen-stimulating coating with Solcoseryl. The laboratory animals were withdrawn from the experiment on the 10th, 30th, 60th, and 90th days. The excised sections of the abdominal wall were stained with G+E to determine the nature of inflammation and the number of cell elements. Results and discussion: When using endoprostheses with a collagen-stimulating coating, the stages of inflammatory process proceeded more quickly, which was confirmed by a reliable (р ≤ 0.05) decrease in the number of neutrophils, macrophages and lymphocytes at all stages of the study. By the 90th day of the experiment, the number of fibroblasts in the control group was by 22.64% less than in the study groups with a coating. Conclusion: A cytological and histological analysis in the control group determined a consistent decrease in an exudative phase of inflammatory reaction. When using endoprosthesis with coatings, its acceleration and lower intensity was noted throughout the study. In the group with Solcoseryl, the formation of a dense connective capsule around the endoprosthesis indicates its quality and better adaptation of the endoprosthesis in body tissues.